PROGRAM EVALUATION OF READING PLUS : STUDY OF THE IMPACT ON READING ACHIEVEMENT FOR STUDENTS WITH DISABILITIES IN MOORE COUNTY SCHOOLS - Simeon, Emilie Lawrence (East Carolina University, 2014)
The Superintendent of the Moore County Schools requested program evaluation for the purpose of determining the effect of remediation programs on achievement for students in the school system. This evaluation examined the intended purposes, actual uses, and benefits of the Reading Plus program on reading skills for Students with Disabilities. Data results from both qualitative and quantitative sources were analyzed to determine impact of the program.   The study revealed that students in grades four though nine participate in the Reading Plus program for remediation purposes. The program, which is based on research regarding eye movements during the reading process, controls the speed of the eye movement during reading and trains the eye to travel more fluidly across written script. Reading Plus curriculum includes the five key reading areas determined by the National Reading Panel of 2000. Results of the study indicate that the Reading Plus program is both cost effective and appropriate for most Students with Disabilities at elementary, middle, and high school levels.
Keywords: Educational leadership; Curriculum; Education; Program evaluation; Reading; Reading--Remedial teaching--North Carolina--Moore County--Aids and devices--Evaluation; Reading (Middle school)--North Carolina--Moore County; Students with disabilities--North Carolina--Moore County; Moore County Schools; Reading plus (Winooski, Vt.)